Kearifan Lokal dalam Bangunan Tradisional di Jawa Barat sebagai Penerapan Konsep Arsitektur Berkelanjutan - Damayanti, Fifi ; Ningrum, Diana (Prosiding SENTIKUIN (Seminar Nasional Teknologi Industri, Lingkungan dan Infrastruktur), 2019)
Local wisdom is an ideas and norm that continuously lives in the society and functioned toregulate the lives of its people. Local wisdom in building architecture is not only related tomystical or religious values that develop in the society. Local wisdom is also a manifestationfrom community's logical thinking about residential or settlement problems. Local wisdom aimsto protect the community and the environment, social-spiritually, economically and physicallyof the community. If sustainable architecture, which is increasingly being developed in thedesign of modern building designs, excavated from the local values of the community certainlywill give an influence on sustainable development. Therefore, this paper aims to learn how localwisdom in traditional buildings accommodates sustainable architectural concepts in terms ofbuilding structure systems; the form, space and material that used in the building; and the useof renewable energy. The method used in understanding this is the theoritical study of Baduy?straditional house Sulah Nyanda and Sundanese?s traditional house in Kampung Naga. Thetheoretical review shows that the local wisdom of the Baduy and Sundanese tribes in traditionalarchitecture has a sustainable architectural concept. This can be an input for designing modernbuildings that are sustainable